The design and efficacy of an antisense oligodeoxynucleotide (ODN) targeted against alpha-I-tubulin of Plasmodium falciparum - Louw, Abraham Izak (University of Pretoria, 2013)
Thesis (PhD (Biochemistry))--University of Pretoria, 2007.